Mode-locked pulse generation in erbium-doped fiber laser by evanescent field interaction with reduced graphene oxide-titanium dioxide nanohybrid - Ahmad, Harith; Reduan, Siti Aisyah; Yusoff, Norazriena; Ismail, Mohammad Faizal; Aidit, Siti Nabila (Elsevier, 2019)
In this work, a new nanohybrid saturable absorber (SA)is successfully fabricated from reduced graphene oxide (rGO)nanosheets and titanium dioxide (TiO2)nanoparticles. The nanohybrid material is synthesized using the simple and inexpensive hydrothermal technique. The SA is fabricated by depositing the nanohybrid solution onto a D-shaped fiber in an erbium-doped fiber (EDF)laser cavity. The evanescent wave interaction between the incident light and rGO-TiO2 nanohybrid material induces mode-locking in the EDF laser at the threshold pump power of 100.80 mW. A stable soliton pulse with a center wavelength of 1560.45 nm and 3-dB bandwidth of 2.47 nm is obtained. The generated pulses have a repetition rate and pulse width of 11.19 MHz and 1.05 ps at the highest pump power of 268.10 mW. The proposed rGO-TiO2 nanohybrid of this work is a promising SA material for generating mode-locking in an EDF laser for optical modulation applications. © 2019